EVALUATION OF BIOCHEMICAL CHARACTERISTICS OF A TRADITIONAL SALT FERMENTED FISH PRODUCT OF NORTHEAST INDIA WITH SPECIAL REFERENCE TO ITS FLAVOUR COMPONENTS - Majumdar, Ranendra Kumar; Basu, S.; Prasad, S. V. (Journal of Indian Fisheries Association, 2015)
"Lona ilish", is a traditional salt fermented fish product, widely consumedand very popular in Northeast part of India and Bangladesh. It is preparedexclusively from a high fat fish, Hilsa (Tenualosa) ilisha. "Lona ilish" wasprepared in the laboratory following traditional process. After 150 days offermentation, a better quality "lona ilish" was obtained. Biochemicalcharacteristics of market sample was estimated and compared with thelaboratory prepared one. A variation in biochemical composition wasobserved. Sensory quality of the final product of laboratory prepared "lonailish" was compared with the market sample and found that the laboratoryprepared product scored better than the market sample. The moisture (49.89%)and salt (15.48%) of the final product was found to be satisfactory for stabilityof the 'lona ilish' at ambient temperature. Analysis of volatile compounds of"lona ilish" was done using GC-MS. It was concluded that, aldehydes, ketonesand esters may possibly contribute characteristic aromas to the overallflavour of the salt fermented hilsa.Key words: hilsa, traditional technology, fermentation, salting, biochemicalcomposition, volatile components